The role of greenway in improving the Klang River corridor at Bandar Klang, Selangor - Airul Anuar, Siti Madihah; Bahari, Noraini (2025)
Greenway is a green, sustainable approach applied in a linear form park and can be in various types of public spaces including waterfront, urban parks, street parks, and many more. This greenway approach offers many benefits, especially connected jogging pathways, bicycle lanes, and habitat corridors for wildlife. However, the problems with applying this method toward our river corridor are still lacking due to anthropogenic factors like plastics, paper, and debris discarded improperly. This includes the issues of dumping areas in the river corridor along the Klang River, Selangor. This study used a direct observation method such as photographic documentation, and a mapping technique to spot the dumping within the area while the measurements were taken, covering aspects such as riparian woodland, roads, sidewalks, active channels, and river channels. The results visualized through the heatmap of the dumping spot in ArcGIS Pro, highlight the optimal strategies implementation. Additionally, the river measurement was analysed using comparative analysis against the ecological standard, revealing that while the dimensions meet the guidelines, they still fall within the minimum requirements. To address this, the study suggests the formation of buffer zones to reduce the narrowing of river sections caused by ongoing urban development. In summary, this research underscores the need for strategic greenway planning and the establishment of a buffer zone to balance ecological integrity and urban growth in the Klang River corridor.